2018
DOI: 10.1159/000486666
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Portal Hypertensive Enteropathy Exacerbation in Patients with Liver Cirrhosis: A Capsule Endoscopy Study

Abstract: Background/Aims: The clinical course and exacerbation of portal hypertensive enteropathy (PHE) are yet to be fully clarified. This study aimed to identify factors related to PHE exacerbation in patients with liver cirrhosis (LC). Methods: Fifty patients with LC (33 male; mean age, 67 years), who underwent capsule endoscopy (CE) at the Hiroshima University Hospital between February 2009 and September 2015, were followed up for >6 months. Exacerbation is defined as the appearance of new lesions or worsening of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…In addition, LC, hematologic disease, and the lowest hemoglobin levels were identified in patients with occult OGIB. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, LC, hematologic disease, and the lowest hemoglobin levels were identified in patients with occult OGIB. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, LC, hematologic disease, and the lowest hemoglobin levels were identified in patients with occult OGIB. 13,14 Regarding rebleeding after treatment, we previously reported that a good outcome could be expected for patients who undergo total enteroscopy and receive proper treatment for the source of bleeding in the small bowel. 15 Aoki and colleagues 16 reported that the rebleeding rate was lower for single ulcerations than for multiple ulcerations in OGIB patients with ulcerative lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnoses were made by consensus. In accordance with a previous report, PHE was defined as the presence of erythema, erosion, angioectasia, varices, and/or villous edema; exacerbation was defined as the appearance of new lesions or worsening of existing lesions in the small-bowel (degree or range) [9]. Villous edema exacerbation is defined as progression of the lesion range and development of severe villous edema, so that identification of the lumen of the smallbowel is no longer possible [11].…”
Section: Ce Proceduresmentioning
confidence: 81%
“…De Palma et al [4] defined these changes as portal hypertensive enteropathy (PHE), which presents as inflammatorylike lesions (edematous, erythematous, granular, and friable lesions) and/or vascular lesions (cherry red spots, telangiectasias, angiodysplasia-like lesions, and varices). In particular, vascular lesions associated with PHE cause small-bowel bleeding, which is a clinically noteworthy finding [8,9]. Previously, we reported capsule endoscopy (CE) as a useful diagnostic modality for detecting PHE in patients with compensated LC [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation